ASSOCIATIED T-CD4 CELL COUNT AND OROPHARYNGEAL CANDIDOSIS IN PATIENTS WITH HIV/AIDS (Vietnam Journal of Community Medicine, 2026)
Oropharyngeal candidiasis (OPC) remains the most common and recurrent opportunistic infection among people living with HIV/AIDS.Objective: This study aimed to evaluate the association between CD4+ T-cell counts and the prevalence of OPC in HIV-infected patients.Methods: A cross-sectional study was conducted among 52 HIV-positive outpatients at Thuan An City Medical Center, Binh Duong Province, from December 2023 to June 2024. Oral swab specimens were collected for fungal isolation and species identification. Absolute CD4+ T-lymphocyte counts were determined using flow cytometry.Results: The overall prevalence of Candida spp. was 57.7%, with Candida albicans being the predominant species (50%). Patients were stratified according to CD4+ T-cell counts into two groups: ≥300 cells/mm³ (53.8%) and
Keywords: Oropharyngeal candidosis, Candida albicans, HIV/AIDS, T-CD4.